TANGGUNG JAWAB PIDANA NOTARIS/ PEJABAT PEMBUAT AKTA TANAH (PPAT) TERHADAP AKTA YANG CACAT HUKUM AKIBAT PELEGALISIRAN YANG TIDAK SAH - ARIANTI, NANI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The aims of this study were to determine and examined criminal responsibility of a notary/PPAT towards a deed that is legally flawed due to an unauthorized legalization, as well as the consequences of the incumbent of the notary/PPAT during the legal process until it is legally enforceable. This research was a normative study, and supported by empirical research (field study). This report was a descriptive analytic, namely the report illustrates norms related to the legal issues associated and supported by the field research. This research was expected to have any legal solution based on the on data obtained. The results of this study were: (1) Criminal responsibility for a notary towards a deed that is legally flawed as a result of the unauthorized legalization, if it can be proven formally that the deed was intentionally (with full awareness and conviction as well as something that has been planned by a particular notary and other parties/the associated concerned) to commit a crime or in the making of a party deed or deed of relaas consciously and intentionally together with the appearers do, help, or order the appearers to perform a legal action that he/she has actually been informed that it was actually an unlawful action